Reinforcing Effects of the Synthetic Cathinone α-Pyrrolidinopropiophenone (α-PPP) in a Repeated Extended Access Binge Paradigm - Nagy, Erin K.; Overby, Paula F.; Olive, M. Foster (Frontiers in Psychiatry, 2020)
Synthetic cathinones are designer psychostimulants that are derivatives of the natural alkaloid cathinone, and produce effects similar to more traditional illicit stimulants such as cocaine and methamphetamine. The pyrovalerone cathinones methylenedioxypyrovalerone (MDPV) and α-pyrrolidinopropiophenone (α-PPP) exert their effects via inhibition of presynaptic dopamine and norepinephrine reuptake transporters. While the reinforcing effects of MDPV in rodents are well-established, very few studies have examined self-administration patterns of α-PPP. Users of synthetic cathinones often engage in repeated binge episodes of drug intake that last several days. We therefore sought to determine the reinforcing effects of three doses of α-PPP (0.05, 0.1 and 0.32 mg/kg/infusion) under conditions of prolonged binge-like access conditions, with three 96-hr periods of drug access interspersed with 72 hr of abstinence. MDPV (0.05 mg/kg/infusion) was used as a comparison drug. Our results show that both MDPV and the high (0.32 mg/kg/infusion) dose of α-PPP are is readily self-administered at high levels across all three extended access periods, whereas lower doses of α-PPP produce variable and less robust levels of self-administration. These results indicate that higher doses of α-PPP have reinforcing effects under conditions of extended access, suggesting the potential for abuse and a need for consideration in drug control policies.